2022
DOI: 10.3390/molecules27092949
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Chemical Compositions and Biological Activities of Mentha suaveolens L. from Saudi Arabia

Abstract: Mentha is an aromatic plant used since antiquity for its pharmaceutical virtues. The climate of Saudi Arabia favors the growth of aromatic plants including Mentha suaveolens L. The aim of this study is to analyze the volatile oils of different parts of fresh and dried Mentha suaveolens L. grown in Saudi Arabia (Aljouf area) using Gas Chromatography/Mass Spectrometry (GC/MS) and Gas Chromatography Flame Ionization Detector (GC/FID) techniques, to recognize the effect of drying on chemical composition, then to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 57 publications
4
8
0
Order By: Relevance
“…Among the different Mentha species, M. suaveolens presented the highest concentration of 4-hydroxybenzoic acid (12.1 mg•g −1 of dry sample) and p-coumaric acid (0.15 mg•g −1 of dry sample) and intermediate levels of rosmarinic acid (1.7 mg•g −1 of dry sample), similar to those present in the M. rotundifolia extract. These compounds have also been previously detected by Aldogman et al [50] in Mentha suaveolens L. leaves from Saudi Arabia at different levels. Low concentrations of luteolin and caffeic acid, characteristic of M. suaveolens ethanolic extracts [26], were also found in this aqueous extract (<0.014 mg•g −1 of dry sample).…”
Section: Lc-ms Characterizationsupporting
confidence: 68%
“…Among the different Mentha species, M. suaveolens presented the highest concentration of 4-hydroxybenzoic acid (12.1 mg•g −1 of dry sample) and p-coumaric acid (0.15 mg•g −1 of dry sample) and intermediate levels of rosmarinic acid (1.7 mg•g −1 of dry sample), similar to those present in the M. rotundifolia extract. These compounds have also been previously detected by Aldogman et al [50] in Mentha suaveolens L. leaves from Saudi Arabia at different levels. Low concentrations of luteolin and caffeic acid, characteristic of M. suaveolens ethanolic extracts [26], were also found in this aqueous extract (<0.014 mg•g −1 of dry sample).…”
Section: Lc-ms Characterizationsupporting
confidence: 68%
“…The Mentha genus is particularly rich in this compound, as well as in chlorogenic and caffeic acid, which were also present in our sample [13,19]. Several authors have also identified rosmarinic acid as the predominant phenolic compound in M. suaveolens extracts [21,59,60]. Rosmarinic acid has been shown to trigger a series of effects on cellular organization and ultrastructures that strongly inhibit the root growth and development of Arabidopsis thaliana [61], also leading to a high inhibitory effect on lettuce radicle elongation [62].…”
Section: Discussionmentioning
confidence: 61%
“…In this case, all the pots corresponding to 4 replicates per treatment for 10 sowing times (80 pots) were concurrently prepared and watered as described in the previous assay. At this time (0 DAI) and every 3 days (3,6,9,12,15,18,21,24,27,30 DAI), four pots were sown with 25, 25, and 15 seeds each of redroot pigweed, barnyard grass, and maize, respectively. Ten days after each sowing time, the emerged seedlings were counted and harvested to obtain the percentage of germination, shoot length, and total aerial biomass (g DW) for each species and the length and biomass of the maize roots (Figure 1).…”
Section: Temporary Phytotoxic Effects Of Apple Mint Biomassmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed information of the essential oils and its composition is provided in Table 1 of some common Mentha species ( Table 1 ). The presence of essential oils indicate that Mentha exhibit high antioxidant, antiinflammatory, and antimicrobial potential, which would help to control the risk of cardiovascular diseases by using Mentha species compounds in food products [ 48 , 49 ].…”
Section: Essential Oil and The Chemical Composition Of The Studied Sp...mentioning
confidence: 99%